Persistence of SARS-CoV-2-IgG antibody durability in convalescent COVID-19 patients 6 months after the natural infection - Qiaoli Hua; Peng Zhang; Shengle Qin; Bing Feng; Bin Xiao; Guangjuan Zheng; Taoyu Ye; Danwen Zheng; Danwen Zheng; Jiayi Mo; Yuntao Liu; Yuntao Liu; et al. (Frontiers in Medicine)
IntroductionLong-term SARS-CoV-2-IgG antibody durability after natural infection remains a critical determinant of long-term protection. However, the factors that affect long-term IgG antibody durability are not fully understood.MethodsThis study delves into the clinical and host genetic factors influencing the level of long-term anti-SARS-CoV-2-receptor-binding domain IgG (RBD-IgG) antibodies after natural infection during the first wave of the COVID-19 pandemic (17 January to 24 June 2020). The cohort, comprising 572 COVID-19 patients from Wuhan, China, had no exposure to COVID-19 vaccines, variants, or antiviral treatments, enabling a focused analysis of the virus’s direct impact.ResultsWe found that the rate of RBD-IgG seropositivity 6 months after infection remained high (94.58%). Through a generalized linear model and mediation analysis, older age, independent of disease severity, was found to be a key independent factor associated with higher post-infection RBD-IgG titers. Hypothesis-generating analyses through a genome-wide association study revealed that rs117929853 (p = 3.6 × 10−8), a variant located upstream of the xanthine dehydrogenase gene (XDH), was significantly associated with RBD-IgG persistence, suggesting a potential mechanistic link between XDH polymorphisms and sustained humoral immunity.ConclusionThe study underscores the significant role of age and genetic factors in the pathogenesis of sustained humoral immunity, which requires further validation.